(untitled) (Swiss Medical Weekly, 2011)
QUESTIONS UNDER STUDY: INR self-testing devices allow patients on vitamin K antagonists (VKA) to determine their INR and then have their VKA dose adapted by a physician (INR self-testing, ST) or adapt it themselves according to pre-established guidelines (INR self-management, SM). The safety, efficacy and advantages of ST and SM have been demonstrated, but their use remains limited. In an effort to improve the availability of ST and SM, we tested the hypothesis that implementing a teaching programme for ST and SM in a small structure in common ambulatory private practice is feasible, safe and can lead to high patient satisfaction. METHODS: Patients on long-term anticoagulation were assigned to a specific training programme. Patients used the CoaguChek (S then XS) INR testing system. Technical problems, adverse events and INR values were then recorded during the first year of follow-up and analysed. Patient satisfaction data were obtained via a specific questionnaire. RESULTS: 169 patients were referred and 90 included in the teaching programme. 80 performed SM and 10 performed ST. 54 patients (60%) returned the 1-year questionnaire with complete INR data available for 35 patients. The percentage of INR in the target range (target ± 0.5) was 60.6%. The rate of major adverse clinical events (MACE) was 3.7 per 100 patient-years. The main reported advantages were a reduction in visits to the INR testing facility and increased autonomy. There was better venous to capillary INR correlation with the CoaguChek XS than with the S (p <0.025). CONCLUSIONS:The development in a small structure in common ambulatory practice of a specific teaching programme made ST and SM available to a new patient population. It led to high patient satisfaction, significantly reducing the burden of VKA monitoring. These results were obtained while preserving the safety and efficacy standards of VKA treatment and favour greater expansion of ST and SM programmes.